Pharmacological Characterization of 5-HT(1A) Autoreceptor-Coupled GIRK Channels in Rat Dorsal Raphe 5-HT Neurons - Montalbano, Alberto (PLoS One, 2015)
G protein-activated inwardly rectifying potassium (GIRK) channels in 5-HT neurons are assumed to be principal effectors of 5-hydroxytryptamine 1A (5-HT(1A)) autoreceptors, but their pharmacology, subunit composition and the role in regulation of 5-HT neuron activity have not been fully elucidated. We sought for a pharmacological tool for assessing the functional role of GIRK channels in 5-HT neurons by characterizing the effects of drugs known to block GIRK channels in the submicromolar range of concentrations. Whole-cell voltage-clamp recording in brainstem slices were used to determine concentration-response relationships for the selected GIRK channel blockers on 5-HT(1A) autoreceptor-activated inwardly rectifying K(+) conductance in rat dorsal raphe 5-HT neurons. 5-HT(1A) autoreceptor-activated GIRK conductance was completely blocked by the nonselective inwardly rectifying potassium channels blocker Ba(2+) (EC(50) = 9.4 μM, full block with 100 μM) and by SCH23390 (EC(50) = 1.95 μM, full block with 30 μM). GIRK-specific blocker tertiapin-Q blocked 5-HT(1A) autoreceptor-activated GIRK conductance with high potency (EC(50) = 33.6 nM), but incompletely, i.e. ~16% of total conductance resulted to be tertiapin-Q-resistant. U73343 and SCH28080, reported to block GIRK channels with submicromolar EC(50)s, were essentially ineffective in 5-HT neurons. Our data show that inwardly rectifying K(+) channels coupled to 5-HT(1A) autoreceptors display pharmacological properties generally expected for neuronal GIRK channels, but different from GIRK1-GIRK2 heteromers, the predominant form of brain GIRK channels. Distinct pharmacological properties of GIRK channels in 5-HT neurons should be explored for the development of new therapeutic agents for mood disorders.